Cibervictimización en el marco de la Teoría de Actividades Rutinarias en la era digital - Morillo Puente, Solbey (2022)
This quantitative-based research determined whether the routine activity theory influences cyber victimization. To measure the dimensions of the theory, defined as exposure to a motivated offender, suitable online target, and absence of a capable guardian, a valid and reliable questionnaire was used. The cyber victimization questionnaire developed by Álvarez-García, Dobarro, and Núñez was applied to 1,285 students selected at random from schools in Colombia. Findings: 46% are identified as exposed to a motivated offender, 37.5% are suitable online targets, and 29.8% have no capable guardians. The interdependence of these three elements revealed that 3.9% of students are at risk due to their routine activities, which had a significant influence on cyber victimization. It is proposed that these findings should be considered in the design of communicative and educational policies aimed at a responsible use of technologies.